TINGKAT PENGORGANISASIAN INTEGRASI INTERNET DI SEKOLAH - Hamzah, Mohd (Proceeding 7th International Seminar on Regional Education, 2015)
Abstract This study aims to determine how high the organization of schools and the integration of the internet in schools. Is there a significant relationship between the two variables? How large is the contribution of the level of organization of the school to the level of integration of the internet in school? Are there differences in the organization of schools and school integration based on school ege. The study used a survey method. The respondents of this study of 75 people. Data were collected using a questionnaire developed by researchers based on their own research construct. Beforethe questionnaire used, analysis ofthe validity and reliability. Based on descriptive analysis shows that the level oforganization ofthe school and the level of integration of the internetin schools at the high category. Based on the analysis of "Product Moment" that there isa significant relationship between the level of organization of the school-level integration of the internet in schools 0.86%, while the contribution rate to the level of organization of school integration of the internetin school was 74.5%. Means, the restis determined by other variables. MANOVA test showed that here was nosignificant difference level of organization and the level of integration of the schools in the school internet based school age.Key word: organization, integration, internet